2017
DOI: 10.1128/genomea.00536-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Two Human Oral Microbiome Commensals: Streptococcus salivarius ATCC 25975 and S. salivarius ATCC 27945

Abstract: Streptococcus salivarius strains are significant contributors to the human oral microbiome. Some possess unique fimbriae that give them the ability to coaggregate and colonize particular oral structures. We present here the complete genomes of Streptococcus salivarius Lancefield K−/K+ strains ATCC 25975 and ATCC 27945, which can and cannot, respectively, produce fimbriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
4
1
Order By: Relevance
“…Regarding the most abundant genera, previous saliva studies reported that Streptococcus was the most abundant genera [24,56,57], which was different from the results of this GCF study. The study by Zaura et al showed that the predominant genera in oral fluid were Streptococcus, Granulicatella, Neisseria, Corynebacterium, Rothia, Actinomyces, Prevotella, Capnocytophaga, Porphyromonas, and Fusobacterium [58].…”
Section: Gcfcontrasting
confidence: 99%
“…Regarding the most abundant genera, previous saliva studies reported that Streptococcus was the most abundant genera [24,56,57], which was different from the results of this GCF study. The study by Zaura et al showed that the predominant genera in oral fluid were Streptococcus, Granulicatella, Neisseria, Corynebacterium, Rothia, Actinomyces, Prevotella, Capnocytophaga, Porphyromonas, and Fusobacterium [58].…”
Section: Gcfcontrasting
confidence: 99%
“…Cigarette smoking has been linked to localized epithelial changes that allow Candidal colonization 25 . Tobacco cigarette smoking may provide nutritional support for Candida growth 113 .…”
Section: Smoking and The Presence Of Oral Candidiasismentioning
confidence: 99%
“…Oral microbiota is not like gut microbiota in changes of bacterial types. Environment and diet have a great influence on the gut microbiota but the same causes have a small effect on oral bacteria 25 . In the previous data collected about oral the human microbiome, about 150 genera, 400 oral taxa, 700 species and over 1300 microorganism strains 26 .…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifactorial and prevalent chronic infectious resulting from tooth-adherent specific bacteria, primarily Streptococcus spp, that metabolize sugars to produce acid, which over time, demineralizes tooth structure (Abranches et al 2018). Streptococcus mitis, S. oralis, and S. salivarius are associated with an initial bacteria tooth-adhesion, which can be used as a bridge to other oral microbiota members such as other streptococci and periodontopathogens (Butler et al 2017). Furthermore, there are reports of meningitis caused by S. salivarius (Falomir et al 2014, Suy et al 2013, Vignier et al 2014; whereas S. oralis and S. mitis can increase virulence factors of Candida albicans (Palma et al 2019) and cause bloodstream infections in pediatric patients (Basaranoglu et al 2019).…”
Section: Introductionmentioning
confidence: 99%